Biomedical signal and image examination with entropy based techniques - Rajinikanth, Venkatesan; Kamalanand, K., 1988-; Emmanuel, C., 1969-; Thayumanavan, B., 1970- (Boca Raton : CRC Press, 2021)
"The aim of this book is to outline the concept of entropy, various types of entropies and their implementation to evaluate a variety of biomedical signals/images. The book emphasizes various entropy-based image pre-processing methods which are essential for the development of suitable computerized examination systems"--
Introduction to entropy and chaos -- Biosignals -- Need for medical imaging and its modalities -- Entropy techniques in image analysis -- Case studies with medical imaging.
OCLC-licensed vendor bibliographic record.
Keywords: Signal processing; Image processing; Entropy; Biomedical engineering; SCIENCE / Biotechnology; TECHNOLOGY / Imaging Systems